Introductory Remarks by World Bank Group President David Malpass at the State of the Global Economy Event Organized by Brookings Institution - Malpass, David (World Bank, Washington, DC, 2022)
These opening remarks were made by World Bank Group President David Malpass at the State of the Global Economy Event Organized by Brookings Institution on July 13, 2022. Mr. Malpass said the world is facing multiple crises, including the sharpest slowdown in GDP growth in 80 years, the risk of a frozen crisis in Ukraine due to Russia's invasion, and a massive worsening in global inequality as advanced economies absorb the limited supplies of global capital and energy. Global growth is not expected to rebound in 2023, given energy supply constraints; the long overdue normalization of interest rates and bond yields in the advanced economies; and the misallocation of investments that has pushed much of the world’s savings into bonds, mostly bonds issued by governments and overcapitalized borrowers. The global economy is also facing significant downside risks. These include intensifying geopolitical tensions, the fragility in many countries, the potential for an extended period of stagflation, the widespread financial stress that's caused by the higher borrowing costs, and food insecurity.